Disparities in who is asked about their perinatal mental health: an analysis of cross-sectional data from consecutive national maternity surveys - Sian Harrison; Victoria Pilkington; Yangmei Li; Maria A. Quigley; Fiona Alderdice (BMC, 2023)
Abstract Background The perinatal period is a vulnerable time, with one in five women experiencing mental health problems. Antenatal and postnatal appointments are key contact points for identifying women in need of support. Since 2014, the UK National Institute for Health and Care Excellence (NICE) has recommended that all women be asked about their mental health at their antenatal booking appointment and early in the postnatal period. The aim of this study was to assess the proportions of women who reported being asked about their mental health during the perinatal period across consecutive national maternity surveys (NMS) in England and to evaluate sociodemographic disparities in who was asked. Methods Secondary analysis was performed on cross-sectional data from the NMS in 2014-2020. In each survey, women reported whether they had been asked about their mental health antenatally (during their booking appointment) and postnatally (up to six months after giving birth). The proportions of women in each survey who reported being asked about their mental health were calculated and compared according to key sociodemographic characteristics and across survey years. Logistic regression was conducted to identify disparities in who was asked. Results The proportion of women who reported being asked about their mental health antenatally increased from 80.3% (95%CI:79.0-81.5) in 2014 to 83.4% (95%CI:82.1-84.7) in 2020, yet the proportion of women who reported being asked postnatally fell from 88.2% (95%CI:87.1-89.3) in 2014 to 73.7% (95%CI:72.2-75.2) in 2020. Ethnic minority women (aOR range:0.20 ~ 0.67) were less likely to report being asked about their mental health antenatally and postnatally across all surveys compared to White women. Women living in less socioeconomically advantaged areas (aOR range:0.65 ~ 0.75) and women living without or separately from a partner (aOR range:0.61 ~ 0.73) were also less likely to report being asked about their mental health, although there was less consistency in these disparities across the antenatal and postnatal periods and across surveys. Conclusions Despite NICE recommendations, many women are still not asked about their mental health during the perinatal period, particularly after giving birth. Women from ethnic minority backgrounds are less likely to be asked and these disparities have persisted over time.